The thermal neutron waves excitation in muldiplied media bounded by absorber - Vodyanitskii, A.A; Slyusarenko, Yu.V. (Вопросы атомной науки и техники, 2007)
An excitation of neutron waves by an external wave source in the active zone of the neutron field is investigated. It is found that the forced neutron waves are transformed into proper (eigen) neutron waves on the borders of the active area. The practical applications of results in noise diagnostics of active area of nuclear reactor are discussed.